Asymmetric tariffs and productivity growth in a endogenous market structure - Colin R. Davis; Ken'ichi Hashimoto (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper constructs a two-country model to investigate how tariff policy influences productivity growth through adjustments in industry location patterns. The locations of production and innovation are determined based on trade barriers and imperfect knowledge dissemination. Tariff policy has the effect of attracting firms, reshaping the location of industry, and the productivity of investment in innovation. We show that the relationship between tariff policy and economic growth depends on the industrial share of the country where the policy is implemented. In addition, examining the welfare effects of tariffs, we find that policy trade-offs may generate positive optimal tariff rates.
Keywords: F43; O30; O40; 330; Tariff Policy; Industry Location; Knowledge Diffusion; Productivity Growth